Intelligent reversible electrochromic flexible electronic fabric based on electronic ink microcapsules. (1st November 2022) - Yin, Chaoyi; Liu, Ruifang; Zheng, Zhangyou; Ba, Long
Abstract: In the last several decades, electronic ink (e-ink) microcapsules have been extensively employed in display screens owing to their high reflectivity and contrast under visible light irradiation, as well as their flexibility, low cost, and low power consumption. Herein, a simple coating technique serves to combine e-ink microcapsules containing multiple color particles with fabrics to design an intelligent reversible electrochromic flexible electronic fabric. E-ink microcapsules, transparent Ag nanowires (T-AgNWs), and single-walled carbon nanotubes (SWCNT) are sequentially and uniformly coated on the surface of the double-layer conductive strip structure composed of conductive fabric and insulating fabric. The electrophoretic discoloration of the e-ink microcapsules can be achieved by applying voltages of a certain magnitude between the bottom conductive fabric strip layer and the T-AgNWs/SWCNT composite conductive layer. Large-area flexible electrochromic fabrics can be formed by weaving strips coated with e-ink microcapsules materials based on the results of the continuous bending and soaking experiments, which has great application potential in the research of adaptive camouflage smart fabrics in the visible light field.